Possible Involvement of Smad Signaling Pathways in Induction of Odontoblastic Properties in KN-3 Cells by Bone Morphogenetic Protein-2: A Growth Factor to Induce Dentin Regeneration - Ayako Washio; Chiaki Kitamura; Takahiko Morotomi; Masamichi Terashita; Tatsuji Nishihara (International Journal of Dentistry)
We examined the effects of bone morphogenetic protein-2 (BMP-2) on growth, differentiation, and intracellular signaling pathways of odontoblast-like cells, KN-3 cells, to clarify molecular mechanisms of odontoblast differentiation during pulp regeneration process. After treatment with BMP-2, the cell morphology, growth, alkaline phosphatase (ALP) activity, and the activation and expression of BMP-induced intracellular signaling molecules, such as Smad1/5/8 and Smad6/7, as well as activities of dentin sialoprotein (DSP) and dentin matrix protein 1 (DMP1), were examined. BMP-2 had no effects on the morphology, growth, or ALP activity of KN-3 cells, whereas it induced the phosphorylation of Smad1/5/8 and expression of Smad6/7. BMP-2 also induced the expressions of DSP and DMP-1. Our results suggest that KN-3 cells may express an odontoblastic phenotype with the addition of BMP-2 through the activation of Smad signaling pathways.